2014
DOI: 10.1371/journal.pone.0093950
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Supervised Classification Methods for the Prediction of Substrate Type Using Multibeam Acoustic and Legacy Grain-Size Data

Abstract: Detailed seabed substrate maps are increasingly in demand for effective planning and management of marine ecosystems and resources. It has become common to use remotely sensed multibeam echosounder data in the form of bathymetry and acoustic backscatter in conjunction with ground-truth sampling data to inform the mapping of seabed substrates. Whilst, until recently, such data sets have typically been classified by expert interpretation, it is now obvious that more objective, faster and repeatable methods of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 44 publications
8
113
0
4
Order By: Relevance
“…The RF classifier is a machine learning function of the wrapper method through the Boruta algorithm [44]. The wrapper function of RF identifies relevant parameters by performing multiple runs of the provided classification factors that test the performance of different subsets of the input parameters [45]. The RF function is a suitable alternative for the analysis of soil parameters at different depths, as it can be employed without extensive parameter tuning and returns an estimate of the feature's importance (Z-score) [46].…”
Section: Selection Of Soil Parameters Using the Random Forest Classifiermentioning
confidence: 99%
“…The RF classifier is a machine learning function of the wrapper method through the Boruta algorithm [44]. The wrapper function of RF identifies relevant parameters by performing multiple runs of the provided classification factors that test the performance of different subsets of the input parameters [45]. The RF function is a suitable alternative for the analysis of soil parameters at different depths, as it can be employed without extensive parameter tuning and returns an estimate of the feature's importance (Z-score) [46].…”
Section: Selection Of Soil Parameters Using the Random Forest Classifiermentioning
confidence: 99%
“…RF also keeps bias low via random predictor selection. RF have been shown to perform well when compared with other rule-based classification approaches, as demonstrated by Stephen and Diesing [52], who reported that tree-based methods, including RF, performed best when predicting sediment classes from acoustic and groundtruth data sets.…”
Section: Discussionmentioning
confidence: 96%
“…This resolution could meet the requirements of ARs management and subsequent classification. The spatial and physical gradients of seafloor, including reef topography and texture were reflected by MBES-derived variables (Hill et al, 2014;Stephens and Diesing, 2014). A suite of acoustic derived datasets was processed using ArcGIS™ for further characterization of benthic habitats.…”
Section: Acoustic Derivative Datamentioning
confidence: 99%
“…Typical unsupervised methods consist of clustering techniques (e.g., k-means and ISODATA) that classify regularities in data sets into seabed acoustic classes (Brown and Collier, 2008;McGonigle et al, 2009). Supervised classification techniques (e.g., artificial neural networks and support vector machines) use ground-truth data to develop a predictive model (Hasan et al, 2012;Huang et al, 2014;Stephens and Diesing, 2014). The main difference between the two classification methods is whether there are enough training samples.…”
Section: Introductionmentioning
confidence: 99%